Menstrual Hygiene Management : A Study of Perception, Problem, and Practices Among Urban Slums of Delhi - Kejriwal, Harshita; Jain, Shubham; Kushwah, Shiksha; Sagar, Mahim; Bansal, Manvi (Indian Journal of Marketing, 2021)
Menstruation starts a new phase in every woman’s life and indicates the initiation of the reproductive period. However, this milestone becomes distinctly painful for women with a lack of awareness and availability of hygienic menstrual products. At many places, the taboo attached to menstruation further adds to this suffering. This scenario is common in the slum communities of developing countries. This study was conducted in the context of urban slums of Delhi, with an aim to understand and assess women’s problems, perceptions, and practices of menstrual hygiene management. It also studied the practices around different absorbents (cloth and pad) and compared the practices around absorbents amongst different user groups (cloth users, pad users, and both). For the study, 1,475 women from 14 urban slums of Delhi were surveyed. The findings of the study indicated the lack of awareness amongst the women regarding menstruation & hygiene practices. Further, affordability, availability, and comfort came out as the key factors influencing the choice of studied absorbents, with affordability being the most important factor. Based on the study’s findings, significant implications for public policymakers and marketers were drawn.